A systematic review of adult pineoblastoma - Chu, Xiufeng; Zhang, Ting; Benghiat, Helen; Xu, Jixuan (Frontiers in Oncology, 2024)
BackgroundAdult pineoblastoma is an extremely rare central nervous system malignancy. Limitations of tumour databases, single institution retrospective analyses and a few case reports are not sufficient to clarify treatment options. Therefore, a systematic review of comprehensive research data provides referenceable treatment options.MethodsA systematic review was performed using MEDLINE and Embase using the terms “pineoblastoma” and “adult”. Relevant articles in the references were considered to supplement this systematic review. In addition, data were analysed using Kaplan-Meier survival curves, COX analysis, chi-square tests and log-rank tests.ResultsA total of 108 adult cases from 32 articles were included in this study and the median age at diagnosis was 30 years. The 5-year survival rate was 49.5% (95% confidence interval: 0.378-0.602) and the 10-year survival rate was 33.9% (95% confidence interval: 0.207-0.476). During the 10-year follow-up period, Kaplan-Meier survival curves highlighted that the gross total resection was more beneficial than subtotal resection and no surgery (P=0.018). The treatment modality of radiotherapy and chemotherapy was beneficial for survival (P<0.001; P=0.020). In addition, multivariate COX analysis showed that radiotherapy was an independent factor in the beneficial prognosis (P<0.001) and gross total resection tends to improve survival within five years (P=0.079).ConclusionFor adult pineoblastoma, gross total excision and radiotherapy can be beneficial for survival.Systematic Review Registration: [website], identifier [registration number].